Poliedros de Arquimedes, Catalan, Kepler-Poinsot, Platão e o Sólido de Escher: contribuições para o ensino e aprendizagem de poliedros - Silva, Ederson Marcelino da (2018)
We present in this work the art of Maurits Cornelis Escher in wich we can visualize polyhedra. We show the historical aspects and studies carried out by Archimedes, Catalan, Kepler, Poinsot and Plato as well as the relation between polyhedra and nature, works of art and architectural constructions. In addition, we deduce a formula for calculating the volume of Escher’s Solid, a stellated rhombic dodecahedron, and we confirm it using GeoGebra and manipulative didactic material. For interactive activities, we suggest applets and digital resources employing the contextualization concomitantly with the theory, contributing to the teaching and learning polyhedra.